Aquiclude Stability Evaluation and Significance Analysis of Influencing Factors of Close-Distance Coal Seams: A Case Study of the Yili No. 4 Coal Mine in Xinjiang, China - Shuaishuai Liang; Dongsheng Zhang; Gangwei Fan; Wenhao Guo; Shouyang Gao; Shuai Zhang; Zhanglei Fan; Wei Yu (Geofluids)
Aquiclude stability is vital for the realization of water-preserving coal mining. And its evaluation, influencing factors, and their significance analysis are quite topical for the ecosystem conservation. The purpose of this paper was to establish an evaluation index system of weakly cemented aquiclude stability. An evaluation index system was built based on three evaluation factors (subsidence, seepage, and deformation), three subfactors (subsidence gradient, seepage rate, and horizontal deformation), and four evaluation criteria (unstable, weakly stable, medium stable, and stable). The evaluation method was applied to evaluate the index for the case study of Yili No. 4 Coal Mine in Xinjiang, China. Based on the geological conditions of the close-distance coal seams in the mine under study, the main influencing factors and subordinate functions of evaluation index Sta were analyzed. The above three factors’ weights were assessed as 0.1095, 0.3090, and 0.5815, respectively, and the proposed evaluation method’s feasibility was verified by the water level variation in the observation hole. The range and variance analyses were performed to assess the significance of the mining heights of the upper and lower coal seams and the coal seam spacing. The results showed that the aquiclude stability negatively correlated with the mining heights and positively correlated with the coal seam spacing. The decreasing order of influence significance on the aquiclude stability was as follows: upper coal seam mining height, lower coal seam mining height, and coal seam spacing. Water protection mining was an effective measure to control the Sta, and the findings provided a reference value and academic significance for the ecosystem conservation.